Regionalizáció, területi reformok és közigazgatási térfelosztás Közép-Európában : 2. rész: Délszláv tanulságok - Gulyás, László (Közép-Európai Közlemények, 2010)
According to literature dealing with the reforms of public administration, the territorial division of a country is purely a professional issue. The political elite should elaborate the division on the basis of geographical, economic and other important characteristics of given country in a way that is harmony with its governing system. But in the countries of Central-Europe this theoretical model is modified because of the presence of national minorities. The paper analyzes the reforms of public administration of different Yugoslav states. As you know Yugoslavia was born twice (1918, 1945) and split twice (1941, 1991). The final conclusion of this paper is the following: from 1918 to nowadays the different Yugoslav states were all for homogenization, and were utilizing both regionalization and regionally for their own purposes.